Embodied Harms: Gender, Shame, and Technology-Facilitated Sexual Violence - Henry, Nicola; Powell, Anastasia (Violence against women, 2015)
Criminality in cyberspace has been the subject of much debate since the 1990s, yet comparatively little attention has been paid to technology-facilitated sexual violence and harassment (TFSV). The aim of this article is to explore the ways in which retraditionalized gender hierarchies and inequalities are manifested in online contexts, and to conceptualize the cause and effects of TFSV as “embodied harms.” We argue that problematic mind/body and online/off-line dualisms result in a failure to grasp the unique nature of embodied harms, precluding an adequate understanding and theorization of TFSV.